Ethnography: A Research Paradigm in Cultural Studies (Bon Voyage, 2019)
Ethnography is a new discipline in humanities and social sciences mainly in cultural studies that befits with the politics of identity. Generally people are stereotyped while they become the subjects of etic perspective. But on the other hand emic perspective of ethnography helps to establish the independent identity of the people that valorizes social recognition also. Positivism is a method in thick description under cultural studies that anchors the logical deduction in research that has affinity with quantitative reading of ethnography. While doing so this article has deployed Clifford Geertz’s notion of thick description because it ensures the accuracy in research findings when the researcher is engaged to study ethnicity and identity.